The snow-image, and other twice-told tales - Hawthorne, Nathaniel, 1804-1864 (Salt Lake City, UT : Project Gutenberg, 1996)
"The Snow-Image, and Other Twice-Told Tales" by Nathaniel Hawthorne is a short story collection published in 1851. This final collection of tales released during Hawthorne's lifetime gathers fifteen stories and sketches spanning nearly two decades of his career. The collection includes both newly written pieces and earlier works, ranging from mysterious tales to historical sketches. Though commercially unsuccessful, the volume represents Hawthorne's last gathering of the short fiction that defined much of his literary career. (This is an automatically generated summary.)
The snow-image: a childish miracle -- The great stone face -- Main Street -- Ethan Brand -- A bell's biography -- Sylph Etherege -- The Canterbury pilgrims -- Old news -- The man of adamant: an apologue -- The devil in manuscript -- John Inglefield's Thanksgiving -- Old Ticonderoga: a picture of the past -- The wives of the dead -- Little Daffydowndilly -- My kinsman, Major Molineux.
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Snow-Image,_and_Other_Twice-Told_Tales
Release date is 1996-05-01
Charles Keller
Keywords: Short stories, American; New England -- Social life and customs -- Fiction; Historical fiction, American